Floristic Survey Of Visconde De Souza Fontes Square, East Side Of The City Of São Paulo, SP - Santo , Juliana Cristina do Espirito; Reis, Julio Cezar dos; Nascimento, Ana Paula Branco do (Technical and Scientific Journal Green Cities, 2021)
The large metropolises have been suffering from the consequences of the accelerated and poorly planned urbanization process, which has drastically affected the green areas of cities, reducing these spaces and directly affecting their biodiversity and conservation. The present work had as its objective the floristic survey of an urban square. The Visconde de Souza Fontes Square, located in the neighborhood of Mooca, East side of the city of São Paulo, was selected. It is managed by the Sub-municipality of Mooca with the cooperation of the Associação Amigos da Praça Visconde de Souza Fontes. There were 49 plant species, including trees (60%), shrubs (20%), palm trees (12%) and herbaceous (8%), distributed within 29 families. It is worth mentioning that there was a classification and quantification of tree, shrub and palm species, thus allowing the calculation of relative abundance. The floristic survey showed that the Fabaceae family presents greater species richness, while the Arecaceae family presents greater abundance of individuals. KEYWORDS: Green Urban Areas, Squares, Biodiversity